MRI Assessment of Sacroiliitis With High-Resolution Protocol. Issue 1 (February 2022) - Berkowitz, Jennifer L.; Mandl, Lisa A.; Burge, Alissa J.; Roberts, John A.; Lin, Bin; Schwartzman, Sergio; Carrino, John A.
Background: Sacroiliac (SI) joint subchondral resorption on high-resolution magnetic resonance imaging (MRI) may be an early sign of the development of sacroiliitis. At our institution, high-resolution intermediate-weighted (proton density) MRI sequences are used in the workup of suspected spondyloarthritis (SpA). Questions/Purpose : We sought to test the hypothesis that SI joint subchondral resorption might be a useful MRI feature in the diagnosis of sacroiliitis. Methods : We retrospectively reviewed the records of patients with suspected SpA from a single rheumatologist's practice from January 1, 2010, to December 31, 2017. Patients had an MRI of the SI joints, using our institution's specialized protocol, and underwent standard physical examination and laboratory evaluation. The sensitivity and specificity of SI joint subchondral resorption in the identification of sacroiliitis were estimated using the clinical diagnosis as the reference standard and from a Bayesian latent class model with conditional dependence. Results : SI joint subchondral resorption on SI joint MRI was highly correlated with a positive diagnosis in patients worked up for axial SpA. It demonstrated superior sensitivity when compared with other MRI features used in the MRI diagnosis of sacroiliitis, such as bone marrow edema pattern, erosion, and ankylosis. Interobserver reliability was high for subchondral resorption. Conclusion : This retrospective study found that subchondral resorption on MRI evaluation of the SI joints appeared to be a sensitive indicator of SpA, potentially of early disease. This imaging feature warrants evaluation in other cohorts of patients suspected of having axial SpA to validate diagnostic performance in diverse populations.